Efficacy and Safety of Megafer® Injection versus Venofer® Injection in Pregnant Women with Iron Deficiency Anemia - Haleema Yasmin,; Ghazala Ishrat,; Quratulain N. Siddiqui,; Sohaib Yahya,; Najia Mansoor ,; Mohsin Ali, (Journal of Basic & Applied Sciences, 2018)
Anemia is the most commonly found blood disorder worldwide in the pregnant women and most frequently it is brought on by nutritional deficiencies giving rise to the typical Iron Deficiency Anemia (IDA). Intravenous administration of iron sucrose, provides a rapid mean to treat this condition by fulfilling the increased body demand of iron. Various alternate brands of iron sucrose injections are now available in the market place but a rationale is to be developed for a preferred product, based on its safety and efficacy. This retrospective comparative analysis is designed to compare two different brands, Megafer® injection and Venofer® injection, containing the same generic compound of Iron Sucrose, in Asian pregnant women with Iron Deficiency Anemia. The outcome measure for efficacy was targeted as the increase in levels of hemoglobin (Hb) after the drug administration, as per the approved protocol. The Hb levels were evaluated through hematological parameters while safety was analyzed by measuring the vital signs and any adverse event reported during the whole study period. Megafer® Injection was found to be as effective and safe as Venofer® Injection, for the short term treatment of IDA in pregnant women.